Silver nanoparticles on UiO-66 (Zr) metal-organic frameworks for water disinfection application - Hui Chen; Chen Qiu; Yiran Jiang; Xinyu Liao; Dan Wu; Mofei Shen; Tian Ding (Food Science and Human Wellness)
Drinking water disinfection is an essential process to assure public health all over the world. In this study, silver nanoparticles (AgNPs) on UiO-66 (Zr) Metal-Organic Frameworks (Ag@UiO-66) is proposed as a potential water disinfection strategy. AgNPs are synthesized using polyvinyl pyrrolidone (PVP) as stabilizing agent, and sodium borohydride as reducing agent are subsequently embedded on UiO-66, a high-stability organometallic framework. The effect of premixing time, reaction time and reactant concentration on the loading rate of AgNPs on UiO-66 was investigated. The maximum load rate of AgNPs on UiO-66 could reach 13% when the premixing time is 3 h, the reaction time is 45 min and the concentration of AgNO3 is 10 μg/mL. The formation of AgNPs loaded on UiO-66 was observed and confirmed with ultraviolet and visible spectrophotometry (UV-Vis), scanning electron microscopy (SEM), infrared emission spectroscopy (IES) and X-ray diffraction (XRD) analysis. Ag@UiO-66 exhibited strong antibacterial activity against both Gram-negative Escherichia coli and Gram-positive Staphylococcus aureus, with minimum inhibitory concentrations (MIC) of 64 and 128 μg/mL, respectively. The germicidal efficacy of Ag@UiO-66 enhanced significantly as the temperature rose from 4 °C to 37 °C. The results indicate that Ag@UiO-66 is potential candidate as a feasible water disinfection material.